Non-invasive Assessment of Fecal Stress Biomarkers in Hunting Dogs During Exercise and at Rest - Zannoni, Augusta; Pietra, Marco; Gaspardo, Alba; Accorsi, Pier Attilio; Barone, Monica; Turroni, Silvia; Laghi, Luca; Zhu, Chenglin; Brigidi, Patrizia; Forni, Monica (Frontiers in Veterinary Science, 2020)
Intense exercise causes to the organism to have oxidative stress and inflammation at the gastrointestinal (GI) level. The reduction in intestinal blood flow and the exercise-linked thermal damage to the intestinal mucosa can cause intestinal barrier disruption, followed by an inflammatory response. Furthermore, the adaptation to exercise may affect the gut microbiota and the metabolome of the biofluids. The aim of the present research was to evaluate the presence of a GI derangement in hunting dogs through a non-invasive sampling as a consequence of a period of intense exercise in comparison with samples collected at rest. The study included nine dogs which underwent the same training regime for hunting wild boar. In order to counterbalance physiological variations, multiple day replicates were collected and pooled at each experimental point for each dog. The samples were collected immediately at rest before the training (T0), after 60 days of training (T1), after 60 days of hunting wild boar (T2) and finally 60 days of rest after hunting (T3). A number of potential stress markers were evaluated: fecal cortisol metabolites (FCM) as a major indicator of altered physiological states, immunoglobulin A (IgA) as an indicator of intestinal immune protection and total antioxidant activity (TAC). Since stool samples contain exfoliated cells, we investigated also the presence of some transcripts involved in gastrointestinal permeability (Occludin [OCLN], Proteinase Activated Receptor-2 [PAR-2]), and in the inflammatory mechanism (Interleukin [IL]-8, IL-6, IL1-b, tumor necrosis factor alpha [TNFa], Calprotectin [CALP], Heme Oxigenase-1 [HO-1]) were also investigated. Finally, the metabolome and the microbiota profiles were analyzed. No variation in FCM and IgA content and no differences in OCLN and CALP gene expression between rest and training were observed. On the contrary, an increase in PAR-2 and HO-1 transcripts, a reduction in total antioxidant activity and a different profile of microbiota and metabolomics data were observed. Collectively, the data in the present study indicated that physical exercise in our model could be considered a mild stressor stimulus.